2020
DOI: 10.1186/s12915-020-00896-z
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and adaptive evolution reshape antioxidant enzymatic system diversity across the phylum Nematoda

Abstract: Background Nematodes have evolved to survive in diverse ecological niches and can be a serious burden on agricultural economy, veterinary medicine, and public health. Antioxidant enzymes in parasitic nematodes play a critical role in defending against host oxidative stress. However, the features of the evolution of antioxidant enzymes in the phylum Nematoda remain elusive. Results Here, we systematically investigated the evolution and gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 87 publications
3
17
0
Order By: Relevance
“…All species from this clade possess genes encoding Nemapores and GRSPs with only Romanomermis culicivorax possessing Defensin-encoding genes (see Figure 2). Clade 2/I nematodes are generally considered to be more basal and have more limited gene complements for other protein families including neuropeptides, antioxidant enzymes, G-protein-coupled receptors (GPCRs) and ATP-binding cassette transporters (ABC transporters) (McCoy et al, 2014; IHGC 2019; Xu et al, 2020; McKay et al, 2021). The reduced AMP arsenal observed in Clade 2/I may indicate that elevated AMP diversity in the Crown Clades (Clade 8-12) originated as a result of gene duplications and/or selective pressures that are not observed in the basal clades.…”
Section: Resultsmentioning
confidence: 99%
“…All species from this clade possess genes encoding Nemapores and GRSPs with only Romanomermis culicivorax possessing Defensin-encoding genes (see Figure 2). Clade 2/I nematodes are generally considered to be more basal and have more limited gene complements for other protein families including neuropeptides, antioxidant enzymes, G-protein-coupled receptors (GPCRs) and ATP-binding cassette transporters (ABC transporters) (McCoy et al, 2014; IHGC 2019; Xu et al, 2020; McKay et al, 2021). The reduced AMP arsenal observed in Clade 2/I may indicate that elevated AMP diversity in the Crown Clades (Clade 8-12) originated as a result of gene duplications and/or selective pressures that are not observed in the basal clades.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed that the proportion of the duplicated BUSCOs (13.1–36.7%) in four mitotic parthenogenetic species was higher than in three meiotic parthenogenetic species (0.4–3.0%). The ratio of these BUSCOs number in root-knot nematodes to M. hapla with 2:1 or 3:1 reached to 26–42% in four mitotic parthenogenetic species, particularly in M. arenaria , while was less than 5% in two meiotic parthenogenetic species [ 34 ] . Thus, the multi-copy nature of far gene in mitotic parthenogenetic species was likely due to their genomic characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Genome assemblies of 58 nematodes were retrieved from Wormbase WBPS10 [ 64 ]. We filtered fragmental genome according to assembly metrics and kept one high-quality assembly for multi-assembly species as described [ 34 ]. We employed the same pipeline to identify FAR proteins in nematode genomes [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al. ( 87 ) reported a higher expression of prdx-2 than prdx-3 in developmental stages of C. elegans . It has been also reported that prdx-2 from C. elegans is more important for protecting against H 2 O 2 than prdx-3 ( 88 ), what is consistent with our results ( Fig.…”
Section: Discussionmentioning
confidence: 99%